The Effect Of E-Service Quality And Perceived Value On Customer Loyalty The Mediation Role Of Customer Satisfaction (Case study on Lazada users) - Nurkholis Akbar; Dwi Cahya , Agus; Diansepti Maharani, Bernadetta (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of E-Service Quality on Customer Satisfaction in digital service environments. The objective is to analyze how dimensions of e-service quality affect customer satisfaction levels. The research employs a quantitative approach using survey data analyzed through validity, reliability, and hypothesis testing. The results indicate that E-Service Quality has a positive and significant effect on Customer Satisfaction. These findings imply that improving efficiency, reliability, responsiveness, and security of online services enhances customer satisfaction and strengthens competitive advantage.